Red blood cell membrane-camouflaged nanoparticles: a novel drug delivery system for antitumor application - Qing Xia; Yongtai Zhang; Zhe Li; Xuefeng Hou; Nianping Feng (Elsevier, 2019)
Erythrocytes (red blood cells, RBCs) are the most abundant circulating cells in the blood and have been widely used in drug delivery systems (DDS) because of their features of biocompatibility, biodegradability, and long circulating half-life. Accordingly, a "camouflage" comprised of erythrocyte membranes renders nanoparticles as a platform that combines the advantages of native erythrocyte membranes with those of nanomaterials. Following injection into the blood of animal models, the coated nanoparticles imitate RBCs and interact with the surroundings to achieve long-term circulation. In this review, the biomimetic platform of erythrocyte membrane-coated nano-cores is described with regard to various aspects, with particular focus placed on the coating mechanism, preparation methods, verification methods, and the latest anti-tumor applications. Finally, further functional modifications of the erythrocyte membranes and attempts to fuse the surface properties of multiple cell membranes are discussed, providing a foundation to stimulate extensive research into multifunctional nano-biomimetic systems. KEY WORDS: Red blood cells, Membrane, Nanoparticles, Drug delivery, Antitumor, Biomimetic nanoparticles